The Thoughts and Religious Understanding of Shaikh Ahmad al-Mutamakkin - Zainul Milal Bizawie (Studia Islamika, 2002)
This paper will assist in filling a gap in the knowledge, as well as invite historians to trace it further. This study is therefore important because it contains an approach that is different, but is the result of studies of Islam in South East Asia, especially of the network of ulama in the 17thand 18th centuries. This study concentrates on textual analysis of the work of al-Mutamakkin, Arsh al Muwahhidin. This work of course is not systematically kept, as it obviously was not intended as a holy book. To produce a map of the thinking and religious understanding of al-Mutamakkin, in this study the author uses an approach that has been offered by Muhammad Abed al Jabiri, namely a structuralist method, historical analysis (the socio-political setting), and critical ideology enhanced by anthropological analysis.DOI: 10.15408/sdi.v9i1.673